The Protective Effects of Omega-3 Fatty Acids Against Exposure of Formaldehyde-induced Oxidative Damage in Prefrontal Cortex of Rats. - Zararsız, İsmail; Kuş, İlter; Yılmaz, H. Ramazan; Pekmez, Hıdır; Ögetürk, Murat; Sarsılmaz, Mustafa (Fırat University, 2004)
Aim: In this study, neurotoxic effects of formaldehyde on prefrontal cortex and protective effects of omega-3 fatty acids against these toxic effects were investigated at biochemical level. Material and method: For this purpose, 21 adult male Wistar rats were divided into three groups. Rats in group I were used as control. Rats in group II were injected every other day with formaldehyde. Rats in group III daily received omega-3 fatty acids with injection of formaldehyde. At the end of 14-days experimental period, all rats were killed by decapitation. Then the brains of rats were removed. The activites of superoxide dismutase (SOD), glutathione peroxidase (GSH-Px) and malondialdehyde (MDA) were determined in the prefrontal cortex specimens by using spectrophotometric methods. Results: In our study, levels of SOD and GSH-Px were significantly decreased, and MDA levels were significantly increased in rats treated with formaldehyde compaared to control. Wherease, it was seen that there was an increase in SOD and GSH-Px enzyme activities, and decrease in MDA levels in rats administered to omega-3 fatty acids with exposure of formaldehyde. Conclusion: It was determined that exposure of formaldehyde caused oxidative damage in prefrontal cortex of rats and this damage was prevented by administration of omega-3 fatty acids.

Amaç: Bu çalışmada, formaldehitin prefrontal korteks üzerine olan nörotoksik etkileri ve bu toksik etkilere karşı omega-3 yağ asitlerinin koruyucu etkisi biyokimyasal düzeyde araştırıldı. Gereç ve yöntem: Bu amaçla, 21 adet Wistar-Albino cinsi erkek sıçan üç gruba ayrıldı. Grup I'deki sıçanlar kontrol olarak kullanıldı. Grup II'deki sıçanlara gün aşırı olarak formaldehit enjekte edildi. Grup III'deki sıçanlara ise, formaldehit injeksiyonu ile birlikte günlük olarak omega-3 yağ asiti verildi. 14 günlük deney süresi sonunda bütün sıçanlar dekapitasyon yöntemi ile öldürüldü. Daha sonra sıçanların beyinleri çıkartılarak, prefrontal korteks örneklerinde süperoksit dismutaz (SOD), glutatyon peroksidaz (GSH-Px) ve malondialdehit (MDA) enzim aktiviteleri spektrofotometrik olarak tayin edildi. Bulgular: Çalışmamızda, formaldehit uygulanan sıçanlarda SOD ve GSH-Px değerlerinin kontrol grubuna göre anlamlı bir şekilde azaldığı, MDA düzeyinin ise yine istatistiksel olarak anlamlı bir şekilde arttığı tespit edildi. Formaldehit maruziyeti ile birlikte omega-3 yağ asiti verilen sıçanlarda, SOD ve GSH-Px enzim aktivitelerinde bir artış olurken, MDA değerinde istatistiksel olarak anlamlı bir düşüş olduğu görüldü. Sonuç: Sıçanlarda, formaldehit maruziyeti sonucu prefrontal kortekste oksidatif hasarın oluştuğu ve bu hasarın omega-3 yağ asitleri uygulaması ile önlendiği tespit edildi.
Sıçan Prefrontal Korteksinde Formaldehit Maruziyetiyle Oluşan Oksidatif Hasara Karşı Omega-3 Yag Asitlerinin Koruyucu Etkisi